Meister Eckhart and Thomas of Erfurt : Modism and the Philosophy of Grammar. - Vinzent, M. (Peeters Publishers & Booksellers, 2020)
"Meister Eckhart and Thomas of Erfurt lived streets away from one another. Thomas was the last great figure of the Modistae, the speculative grammarians who were concerned with the relationship between grammar and ontology, the structure of the sentence mirroring the structure of the world. Thomas' major work - the 'Grammatica speculativa' - was deeply influential in the medieval period. But does Thomas' geographical proximity to Eckhart suggest a concomitant influence of modism on his thought? What of modism's legacy after the rapid demise of the grammatical theory in the early-mid fourteenth century? The contributions to this volume deal with these matters, and were originally presented at the 'Meister Eckhart and Thomas of Erfurt' conference at the Max-Weber-Center at the University of Erfurt, 14-15 November 2013." --Provided by publisher, back cover.
Description based upon print version of record.
Keywords: Eckhart, -- Meister, -- -1327.; Thomas, -- von Erfurt, -- active 14th century -- Influence.; Eckhart, -- Meister, -- -1327; Thomas, -- von Erfurt, -- active 14th century; Speculative grammar.; Grammaire spéculative.; PHILOSOPHY / History & Surveys / Medieval; Influence (Literary, artistic, etc.); Speculative grammar; Electronic books.